N‐Terminal Modification of Gly‐His‐Tagged Proteins with Azidogluconolactone - Brune, Karl D.; Liekniņa, Ilva; Sutov, Grigorij; Morris, Alexander R.; Jovicevic, Dejana; Kalniņš, Gints; Kazāks, Andris; Kluga, Rihards; Kastaljana, Sabine; Zajakina, Anna; Jansons, Juris; Skrastiņa, Dace; et al. (Chembiochem : a European journal of chemical biology, 2021)
Site‐specific protein modifications are vital for biopharmaceutical drug development. Gluconoylation is a non‐enzymatic, post‐translational modification of N‐terminal HisTags. We report high‐yield, site‐selective in vitro α‐aminoacylation of peptides, glycoproteins, antibodies, and virus‐like particles (VLPs) with azidogluconolactone at pH 7.5 in 1 h. Conjugates slowly hydrolyse, but diol‐masking with borate esters inhibits reversibility. In an example, we multimerise azidogluconoylated SARS‐CoV‐2 receptor‐binding domain (RBD) onto VLPs via click‐chemistry, to give a COVID‐19 vaccine. Compared to yeast antigen, HEK‐derived RBD was immunologically superior, likely due to observed differences in glycosylation. We show the benefits of ordered over randomly oriented multimeric antigen display, by demonstrating single‐shot seroconversion and best virus‐neutralizing antibodies. Azidogluconoylation is simple, fast and robust chemistry, and should accelerate research and development. Site‐selective α‐amino acylation of proteins with N‐terminal Gly‐HisTags using 6‐azido‐6‐deoxy‐glucono‐1,5‐lactone (6AGDL) is reported. To demonstrate the usefulness of this reaction, we multimerise the SARS‐CoV‐2 receptor‐binding domain (RBD) protein antigen onto virus‐like particles (VLPs) via strain‐promoted alkyne‐azide cycloaddition (SPAAC). The resulting COVID‐19 vaccine candidate induces single‐shot seroconversion, and virus‐neutralizing antibodies in mice.